Elements of Social Media Marketing: A Holistic Framework in Online Culinary - Lina Setiawati; Nono Wibisono (P3M Politeknik Negeri Bali, 2020)
Consumer's lifestyle has been greatly shifted due to the massive development of social media and brought unprecedented opportunities and challenges for marketing activities. There are few steps leading to consumer in deciding the product that they want to buy. This study helps to explain elements and consequences of social media marketing in Instagram context and its relationship with purchase intention. To this end, an empirical study applying partial least square (PLS) were conducted. Utilizing 254 of sample size, the results reveal that community building is crucial determinants of social media marketing in online culinary information search which later affects purchase intention. Further, this study clarifies creating brand identity in Instagram is a way to build a brand image. This research has a potential impact to provide renewed insights for researchers into determinants and consequences of individual purchase intention.